Character Building and The Awareness on The Importance of Caring for The Earth - Yusuf Olang (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
Environmental damage is getting worse in developing countries including Indonesia, so there is no guarantee that our children and grandchildren will live comfortably and safely in the years to come. The most fundamental thing that causes the rampant exploitation and destruction of the environment is the lack of awareness of the importance of caring for the earth. This awareness will grow along with beliefs and ideologies that become principles in people's lives. Destruction and exploitation of the earth cannot be stopped if the awareness and outlook on the meaning of the earth for human life are not grown starting from this very moment. Efforts to invite the public to respect and care for the environment often face resistance because it is propaganda. Literature has been proven to have the strength and ability to inspire, touch the human heart, move and foster awareness of the importance of caring for the earth and everything because humans and the earth are interdependent.